Making our industrial heritage work for the future, in the context of climate change - Miles Kenneth Oglethorpe (Acta Polytechnica CTU Proceedings)
As Climate Change continues to drive major changes in policy and practice on a global scale, the role of industrial heritage is becoming increasingly important. There remains strong pressure from business interests to clear away the past and start again from a blank canvas, but now there are growing arguments for an alternative approach which re-cycles the carbon already invested in industrial buildings and structures and gives them a second life. There is also an increasing number of examples that demonstrate the power of industrial heritage to drive sustainable regeneration and re-vitalization schemes across the world. Significantly, this trend is not confined to the most attractive, aesthetically pleasing structures – a wide variety of industrial sites have been imaginatively adapted to a new life and in many cases have helped engineer a vibrant future for previously marginalised communities and areas. In Scotland, our national heritage body, Historic Environment Scotland, recently published it’s ‘Climate Action Strategy’. At its heart is the ambition to transform the challenge facing us from one in which our heritage is a victim, instead harnessing it and all its attributes in the battle against Climate Change. This paper will argue that industrial heritage is especially well placed to do this.